Fouling of ultrafiltration membrane during adsorption of long chain fatty acid in glycerine solutions - Indok Nurul Hasyimah Mohd Amin (Universiti Kebangsaan Malaysia, 2014)
Publsihed in ISI Journal. Full text article also available in http://www.ukm.my/jsm/pdf_files/SM-PDF-42-6-2013/16%20Abdul%20Wahab.pdf